Tensile split Hopkinson bar laboratory tests with imperfect dimension - Goh, Sean Shun Hui (Nanyang Technological University, 2022)
There are 3 kinds of Split Hopkinson Pressure Bar (SHPB) apparatus, which can be found in the Strength of Materials laboratory, located in Nanyang Technological University (NTU) Singapore. Based on different dynamic loading conditions through tension, torsion, and compression, the apparatus is used to achieve the mechanical properties of various materials which are subjected to high strain rates. For this report, the focus will be on the dynamic tension SHPB. The tensile SHPB is used to obtain the dynamic stress and strain response under tension, subjected to high strain rates which ranges from 102 to 104 S-1. The main theory is based along the elastic bars, where there is an occurrence of propagation of longitudinal stress waves. Strain gauges are attached on the incident and transmitted bar. Thereafter, to collect the raw data, an oscilloscope is used to transfer the voltage signal readings retrieved from the strain gauges. After the data is collected, strain vs time, stress vs strain, and strain rate vs time curves are generated, which are then compared against with past literature reviews. The objective of this project is to obtain the tensile stresses of alloys subjected to high strain rates. It is also to certify that the SHPB apparatus setup located in NTU is reliable, and repeatable for future projects. Empty run and calibration run of SHPB were conducted by using the specimen Al6061-T6, with varying insertion distances. The results obtained are then compared to past year reports to ensure that it is repeatable for future projects. The project will also study how the mechanical properties of the specimen piece will be affected by varying the insertion distance of the striker bar into the gas chamber, which gives varying impact velocities. Additionally, the effects of an imperfection on the mechanical properties of the specimen piece will be investigated. Lastly, a conclusion of the entire project, issues faced during the project, and recommendations will be suggested on how to further improve on the project will be included at the end of this report.